La transmission transgénérationnelle des traumas dans La plus secrète mémoire des hommes (Revista Cercurilor studenţeşti ale Departamentului de Limba şi Literatura Franceză, 2025)
Mohamed Mbougar Sarr’s novel is part of the trend of so-called “memorial” literature, dealing with the traumatic history of colonization, colonial racism and the Shoah, but also with the civil war in the Congo and the current disarray of African societies in the face of their political elites. He talks about the “ghetto” of the African diaspora in Paris and, in the background, he returns tothe negritude movement and the vision of the world and of French-speaking African literature promoted at the time by Léopold Sédar Senghor. La plus secrète mémoire des hommes contains many cultural references distilled through the discourse of its narrator, the author’s alter ego, but the most important aspect to emphasize from the outset is Mohamed Mbougar Sarr’s bias against the current doxa in French literature, which sees literature as a more complex and refined substitute for individual, family or group psychological therapy. His work shows collective traumas and their repercussions on an individual level, portrays the transgenerational transmission of traumas, and highlights traumatic memory, the unspeakable, and even the question offorgiveness. For all that, it remains a plea for literature that could be described as “immemorial”, timeless and universal. Literature that is written not to save the world, but to save it through its beauty.
Keywords: trauma representation; transgenerational transmission of traumas; Mohamed Mbougar Sarr